Seasonal Variation in Chemical Composition and Antioxidant and Antibacterial Activity of Essential Oil from Cinnamomum cassia Leaves - Yanrong Cheng; Ying Fu; Dingze Gu; Yan Huang; Yongqi Lu; Yujie Liu; Xiulan Li; Xinyue Yao; Xinxuan Zhang; Wanying Jian; Peiwei Liu; Hong Wu; et al. (Plants)
Cinnamomum cassia has been extensively utilized in traditional medicine systems worldwide. The essential oil (EO) content and composition are influenced by various external and internal factors, such as climate and harvest season, making it vital to determine the optimal harvest period for high-quality EO production. This study is the first to evaluate the chemical profiles, as well as the antioxidant and antibacterial activities, of C. cassia leaf oil across the four seasons. GC–MS and FTIR analyses revealed significant seasonal variations in the components. Spring and autumn leaf oils contained the highest EO (2.20% and 1.95%, respectively) and trans-cinnamaldehyde (92.59% and 91.10%, respectively). Temperature and humidity primarily affected EO and trans-cinnamaldehyde accumulation. C. cassia leaf oil demonstrated the strongest antibacterial activity, with a minimum inhibitory concentration (MIC) of 0.25 mg/mL against S. aureus and L. monocytogenes for the spring oil. The MICs for the other three seasonal samples were 0.5 mg/mL for S. aureus, M. luteus, and L. monocytogenes, and 1.0 mg/mL for P. putida. The minimum bactericidal concentration (MBC) of the EOs across all seasons against S. aureus ranged from 0.5 to 1 mg/mL. Winter leaf oil exhibited high antioxidant activity, primarily due to the presence of cis-cinnamaldehyde, caryophyllene, humulene, alloaromadendrene, γ-muurolene, cis-bisabolene, o-methoxycinnamaldehyde, and phenolics. This study provides essential data and valuable references for optimizing resource utilization and determining the ideal harvest time for C. cassia leaves.